Correction: Long-term in situ permafrost thaw effects on bacterial communities and potential aerobic respiration - Monteux, Sylvain; Weedon, James T.; Blume-Werry, Gesche; Gavazov, Konstantin; Jassey, Vincent E.J.; Johansson, Margareta; Keuper, Frida; Olid, Carolina; Dorrepaal, Ellen (The ISME Journal, 2019)
Since the publication of the original article, the authors noticed some errors in reference citation had been introduced throughout the paper. The following text contains excerpts from the original article and how they should appear with correct referencing. The publisher apologises for any inconvenience this has caused readers.